LB0007 SUBCUTANEOUS TANEZUMAB FOR OSTEOARTHRITIS PAIN: A 24-WEEK PHASE 3 STUDY WITH A 24-WEEK FOLLOW UP. (June 2019) - Berenbaum, Francis; Blanco, Francisco J.; Guermazi, Ali; Vignon, Eric; Miki, Kenji; Yamabe, Takaharu; Viktrup, Lars; Junor, Rod; Carey, William; Brown, Mark; Verburg, Ken; West, Christine
Abstract : Background: Tanezumab, a monoclonal antibody against nerve growth factor, is in development for treatment of osteoarthritis (OA) pain. Objectives: To assess efficacy and safety of tanezumab in patients with moderate to severe OA pain who have not responded to or cannot tolerate standard of care analgesics. Methods: A randomized, double-blind, placebo-controlled study (24 week treatment; 24 week follow-up) was conducted in patients in Europe and Japan with moderate to severe OA pain of the knee or hip and history of insufficient pain relief or intolerance to acetaminophen, oral nonsteroidal anti-inflammatory drug, and either tramadol or opioids (or unwilling to take opioids). Patients received subcutaneous tanezumab (2.5 or 5 mg) or placebo at baseline, week 8, and week 16. Co-primary endpoints were change from baseline in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain, WOMAC Physical Function, and Patient Global Assessment of OA (PGA-OA) scores at week 24. Safety, including independent adjudication of joint safety events, was assessed. Results: Tanezumab 5 mg met all co-primary endpoints (Fig. 1). Tanezumab 2.5 mg met WOMAC Pain and Physical Function endpoints but not the PGA-OA endpoint; thus, this dose did not meet pre-specified efficacy criteria. The occurrence of adverse events (AEs) and discontinuations due to AEs were similar across groups, though serious AEs occurred more frequently in both tanezumab groups relative to placebo. Two deaths in the 5 mg tanezumab group were deemed unrelated to treatment. The only AE occurring in =3% of patients in any group, and more frequently (>1% difference) in both tanezumab groups relative to placebo, was OA. Total joint replacements (TJR) occurred in 6.7%, 7.8%, and 7.0% of patients in the placebo, tanezumab 2.5 mg, and tanezumab 5 mg groups, respectively. Joint safety events, including TJRs, were mostly adjudicated as normal progression of OA (58/79; 73.4%). Pre-specified joint safety events occurred in 0% and 2.5% (n = 14) of patients in the placebo and tanezumab (2.5 mg = 1.8%; 5 mg = 3.2%) groups, respectively. These 14 events in the tanezumab groups included rapidly progressive OA (2.5 mg n = 4; 5 mg n = 8), subchondral insufficiency fracture (2.5 mg n = 1), and primary osteonecrosis (5 mg n = 1). Conclusion: Tanezumab 5 mg significantly improved all co-primary endpoints of pain, physical function, and PGA-OA. Tanezumab 2.5 mg significantly improved pain and physical function, but did not reach significance on PGA-OA. AEs are consistent with previous studies of tanezumab in OA. A similar number of TJRs were reported across groups, though overall joint safety events were more frequent with tanezumab than placebo. Disclosure of Interests: Francis Berenbaum Grant/research support from: TRB Chemedica (through institution), MSD (through institution), Pfizer (throughinstitution), Consultant for: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Bone Therapeutics, Regulaxis, Peptinov, Paid instructor for: Sandoz, Speakers bureau: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Sandoz, Francisco J. Blanco Grant/research support from: Galapagos NV, Abbvie, Sanofi, Bristol MS, UCB, Novartis, Genentech Inc., Regeneron, Lilly, Celgene, Amgen, Janssen, kiniksa Pharmaceuticals, Ltd., Tedec Meiji., Consultant for: Pfizer, Gebro, Bioiberica, Sanofi., Ali Guermazi Consultant for: AstraZeneca, Pfizer, TissueGene, Galapagos, Roche and MerckSerono., Eric Vignon Consultant for: Pfizer/Eli Lilly, Kenji Miki Speakers bureau: Pfizer, Janssen, Ayumi, Hisamitsu, Takaharu Yamabe Shareholder of: Pfizer, Employee of: Pfizer, Lars Viktrup Shareholder of: Eli Lilly & Company, Grant/research support from: Astella, Lundbeck, Coloplast, Employee of: Ciba Geigy, Eli Lilly and Company (currently), Rod Junor Shareholder of: Pfizer, Employee of: Pfizer, William Carey Shareholder of: Pfizer, Employee of: J&J, Pfizer (currently), Mark Brown Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ken Verburg Shareholder of: Pfizer, Employee of: Pfizer, Christine West Shareholder of: Pfizer, Employee of: Pfizer